Clinical and prognostic value of endothelin-1 and big endothelin-1 expression in children with pulmonary hypertension. Issue 13 (8th March 2016) - Latus, Heiner; Karanatsios, Georg; Basan, Ulrike; Salser, Kirstin; Müller, Simon; Khalil, Markus; Kreuder, Joachim; Schranz, Dietmar; Apitz, Christian
Abstract : Objective: Pulmonary arterial hypertension is known to be associated with increased expression of endothelin (ET)-1 and its precursor big ET-1. Therefore, we hypothesised that in children with pulmonary hypertension (PH) altered levels of ET-1 and big ET-1 may have clinical and prognostic impact. Methods: Sixty-six children with different forms of PH (mean age 10.4±9.7 years) were included. Blood samples were taken from the pulmonary artery and a systemic artery. Levels of ET-1/big ET-1 were measured via ELISA method and compared with clinical and haemodynamic data. To assess prognostic relevance, Kaplan–Meier survival analysis was conducted with definition of end point as the composite of mortality, lung transplantation, use of intravenous prostanoids and Potts shunt creation. Results: ET-1 levels ranged between 0.09 and 11.64 (mean 1.48±2.34) fmol/mL, and big ET-1 levels between 0.05 and 2.92 (mean 0.84±0.58) fmol/mL. No significant relationships were found between ET-1/big ET-1 levels and functional class as well as haemodynamic indices of PH severity. Mean follow-up after catheterisation was 63.2±44.1 months. While 31 of the 66 (47%) patients with PH reached a predefined end point, there was no significant relation between levels of ET-1/big ET-1 and patient outcome. Conclusions: Although children with PH had alterations in ET-1/big ET-1 expression, which may reflect changes in net release or lung clearance, levels of ET-1/big ET-1 showed no correlation with clinical and haemodynamic parameters, and were not able to predict outcome.